Determination of Beryllium and Major Elements in Beryllium Ores by Inductively Coupled Plasma-Optical Emission Spectrometry with Lithium Metaborate Fusion - Lin GUO; Tingting YU; Hongbin SUN; Yun ZHU (Yankuang ceshi)
At present, the systematic analysis method of beryllium ores is still dominated by the traditional chemical method, which seriously affects the analytical efficiency. It is necessary to develop a simple and efficient multi-element analysis method in beryllium ores. We establish a quantitative analysis method for beryllium and principal elements in beryllium ores based on lithium metaborate fusion-inductively coupled plasma-optical emission spectrometry (ICP-OES) to overcome the limitations of the traditional acid solubilization or alkaline fusion that cannot detect elements such as silicon, sodium and potassium. The method involves mixing the flux and the sample in a 4∶1 ratio, melting at 950℃ for 15min, and preparing solutions through ultrasonic extraction. The matrix effect is eliminated by matrix matching and adding europium (Eu) as the internal standard. The content of beryllium oxide in the experimental sample is between 0.14% and 13.33%. The experimental results show that the precision and accuracy of this method meet the quality control requirements in the quality management specification of the geological and mineral laboratory. It is suitable for the continuous and rapid determination of beryllium and major elements in many types of beryllium ore samples such as beryl, hsianghualite and helvine.